Minimum wage, business dynamism, and the life cycle of firms - André Victor Doherty Luduvice; Tomás R. Martínez; Alexandre B. Sollaci (Inter-American Development Bank (IDB), 2024)
This paper studies the effects of the minimum wage on the life cycle of firms. We first build a tractable model where heterogeneous firms have labor market power, invest in innovation, and choose formal or informal sectors. The model predicts that a minimum wage hike not only shrinks young and low-productivity firms but also lowers incentives to innovate, resulting in lower life cycle growth. We then test the predictions of the model using Brazilian administrative and census data leveraging the variation in exposure across establishments and municipalities to the large increase in the minimum wage between 1999 and 2010. At the establishment level, an increase in the minimum wage: i) decreases the growth rates of small and young establishments and ii) increases the growth rates of old and large establishments. When analyzing exposed municipalities, we observe an increase in the earnings of workers in both the formal and informal sectors, as well as informal employment. Our findings suggest that the minimum wage is a possible explanation for the decline in the importance of young establishments and business dynamism in Brazil.
Keywords: J38; J42; E24; E26; L25; 330; Minimum wage; Business dynamism; Monopsony; Firm heterogeneity; Informality